Cross platform mobile application development : a comparison study of React Native Vs Flutter - Fentaw, Awel Eshetu (2020)
With a dramatic increase in the usage of handheld devices such as smartphones and tablets, it became a matter of existence for businesses if they do not deliver their services to address mobile users. One critical problem for businesses to address these massively growing users is the diversity of mobile platforms that users prefer to use. Businesses need to find a way for their service to run in different mobile platforms using a single code base or very minimal platform specific tweaks. Hence cross-platform mobile application development comes to the rescue. Among the widely used cross-platform mobile application development kits are React Native and Flutter. React Native is an open-source mobile application development framework created by Facebook. Developers can develop applications for mobile and web by using React. React is a declarative, component-based JavaScript library for building user interfaces (UI). Another important UI toolkit is Flutter. Flutter is Google’s UI toolkit for developing natively compiled applications for mobile, web and desktop from a single code base written using Dart. This thesis presents a comparison study of two widely used cross-platform mobile application development kits. It starts by discussing common application development methodologies. Following that, this thesis details mobile application development approaches with high emphasis on cross-platform mobile application development using React Native and Flutter. There is an implementation of COVID-19 tracking application which consumes REST (Representational State